Acupuncture treatment on the motor area of the scalp for motor dysfunction in children with cerebral palsy: study protocol for a multicenter randomized controlled trial - Wang, Jun (Trials, 2020)
BACKGROUND: Scalp acupuncture has been widely used as treatment for motor dysfunction in children with cerebral palsy in China. Previous studies have failed to provide high-quality evidence to demonstrate the effectiveness of this treatment in children with cerebral palsy. No high-quality randomized controlled trials on scalp acupuncture have been published. The aim of this study is to evaluate the effectiveness of Jiao’s scalp acupuncture when combined with routine rehabilitation treatment versus routine rehabilitation treatment alone for motor dysfunction in children with cerebral palsy. METHODS/DESIGN: This is a four-centre randomized controlled trial. One hundred cerebral palsy patients with motor dysfunction were enrolled. Patients will be allocated in a 1:1 ratio into either an acupuncture treatment group or a control group. Cerebral palsy patients in the control group will receive conventional rehabilitation treatment, whereas patients in the acupuncture group will receive a combination of scalp acupuncture and conventional rehabilitation treatment. Thirty-six treatment sessions will be performed over a 12-week period. The Gross Motor Function Measure and the Fine Motor Function Measure Scale will be assessed as the primary outcome measures. The Paediatric Evaluation of Disability Inventory and the Cerebral Palsy Quality of Life Questionnaire for Children will be selected as secondary outcome measures. All assessments will be conducted at baseline, week 4 (treatment 12), week 8 (treatment 24), week 12 (treatment 36) and week 24 (follow-up). DISCUSSION: This is the first trial evaluating the efficacy and safety of scalp acupuncture as a treatment for motor dysfunction in children with cerebral palsy. The results of this trial are expected to provide relevant evidence demonstrating that scalp acupuncture can be used as an effective rehabilitation treatment method for improving motor dysfunction in children with cerebral palsy. TRIAL REGISTRATION: ClinicalTrials.gov, NCT03921281. Registered on 19 April 2019.